2020
DOI: 10.3390/plants9101267
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Transcriptome and Proteome Analysis Identifies Major Molecular Regulation Pathways Involved in Ramie (Boehmeria nivea (L.) Gaudich) under Nitrogen and Water Co-Limitation

Abstract: Water and N are the most important factors affecting ramie (Boehmeria nivea (L.) Gaudich) growth. In this study, de novo transcriptome assembly and Tandem Mass Tags (TMT) based quantitative proteome analysis of ramie under nitrogen and water co-limitation conditions were performed, and exposed to treatments, including drought and N-deficit (WdNd), proper water but N-deficit (WNd), proper N but drought (WdN), and proper N and water (CK), respectively. A total of 64,848 unigenes (41.92% of total unigenes) were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 64 publications
(70 reference statements)
1
5
0
Order By: Relevance
“…Under DS conditions, N fertilizer application increased the biomass, RWC, and pod yield by 12.10%, 36.84%, and 14.87%, respectively. Overall, N fertilizer application mitigated the adverse effects caused by DS, which is consistent with a previous study [17].…”
Section: Peanut Growth Under Different Water and N Conditionssupporting
confidence: 92%
See 3 more Smart Citations
“…Under DS conditions, N fertilizer application increased the biomass, RWC, and pod yield by 12.10%, 36.84%, and 14.87%, respectively. Overall, N fertilizer application mitigated the adverse effects caused by DS, which is consistent with a previous study [17].…”
Section: Peanut Growth Under Different Water and N Conditionssupporting
confidence: 92%
“…DS and N deficiency are essentially the key limiting factors for peanut growth [13,16], and the combination of nutrient deficiency and DS exacerbates adverse effects [17]. It has been demonstrated that appropriate N application can alleviate the adverse effects of DS The gene products/metabolites with red/green background boxes belong to the differential genes/metabolites detected in this study, where red represents upregulated genes/metabolites and green represents downregulated genes/metabolites.…”
Section: Peanut Growth Under Different Water and N Conditionsmentioning
confidence: 71%
See 2 more Smart Citations
“…Transcriptome analysis of tissue-specific expression was conducted using four different tissue samples of “Zhongzhu No.1” sequenced by our laboratory. Transcriptome data of water deficit and nitrogen deficit were obtained from [ 73 ]. The additional “Zhongzhu No.2” ramie transcriptome changes in leaves of 3-week-old seedlings exposed to waterlogging for 12 h and to normal conditions were profiled using RNA-Seq data in our recent research.…”
Section: Methodsmentioning
confidence: 99%